Association of ambient sulfur dioxide with stroke incidence among residents of Shanghai: a time-series analysis of incidence registration and monitoring data from 2017 to 2021 - Yuzhuo WANG; Xuena LA; Mengyin WU; Yingquan WANG; Danni LIU; Qundi YANG; Yang ZHENG; Yan SHI (Zhongguo gonggong weisheng, 2025)
ObjectiveTo investigate the correlation between atmospheric sulfur dioxide (SO2) and the incidence of stroke in residents of Shanghai city, and to provide a reference for the development of stroke prevention and control measures. MethodsData on 263 872 new stroke cases reported to the Shanghai Stroke and Acute Myocardial Infarction Registry Information System from 2017 through 2021 were collected. Daily mean concentrations of atmospheric pollutants-including SO2, nitrogen dioxide (NO2), ozone (O3), particulate matter with an aerodynamic diameter < 2.5 μm (PM2.5), and particulate matter with an aerodynamic diameter < 10 μm (PM10), as well as meteorological factors such as daily average temperature and relative humidity, were obtained from the national air pollution monitoring stations of the Ministry of Ecology and Environment during the same period. A generalized additive model with a quasi-Poisson distribution link function was used to analyze the time-series relationship between atmospheric SO2 concentration and the daily number of stroke cases. ResultsThroughout the study period conducted in Shanghai, the average daily incidence of registered stroke cases was 145 ± 28, while the mean daily concentration of SO2 was measured at 8.00 ± 3.71 µg/m3. The analysis of the single-day lag model demonstrated that a 10 µg/m³ increase in the mean SO2 concentration was significantly associated with percentage changes (%) in daily stroke incidence across different populations and lag days, as follows: 1. General population: Decreases of 0.21%, 0.28%, 0.29%, and 0.21% were observed at lag days 7, 8, 26, and 27, respectively, while increases of 0.16%, 0.34%, 0.33%, 0.42%, 0.32%, and 0.20% were noted at lag days 19, 20, 21, 22, 23, and 24, respectively. 2. Males: A 0.37% decrease was observed at lag day 26, whereas increases of 0.47%, 0.36%, 0.61%, and 0.33% were recorded at lag days 20, 21, 22, and 23, respectively. 3. Females: A 0.40% increase was observed at lag day 0. 4. Residents aged 60 years and above: Decreases of 0.33% and 0.36% were observed at lag days 8 and 26, respectively, while increases of 0.35%, 0.32%, 0.41%, and 0.32% were noted at lag days 20, 21, 22, and 23, respectively. All reported associations were statistically significant (P < 0.05). Multi-day lag model analysis yielded results consistent with those from the single-day lag analysis: 1. General population: Increases of 16.84%, 18.40%, and 17.95% were observed at lag days 0 - 24, 0 - 25, and 0 - 26, respectively. 2. Males: Increases of 16.73%, 21.09%, 22.39%, and 21.80% were observed at lag days 0 - 23, 0 - 24, 0 - 25 d, and 0 - 26, respectively. 3. Females: An increase of 4.10% was noted at lag days 0-1.4. Residents aged < 60 years: Decreases of 8.60%, 9.89%, 9.36%, 10.67%, 10.98%, and 11.38% were observed at lag days 0 - 4, 0 - 5, 0 - 6, 0 - 7, 0 - 8, and 0 - 9, respectively. 5. Residents aged 60 years and above: Decreases of 15.91%, 19.18%, 20.22%, and 18.99% were observed at lag days 0 - 23, 0 - 24, 0 - 25, and 0 - 26, respectively (all P < 0.05). ConclusionsThe elevated atmospheric SO2 concentration exhibited a significant correlation with a higher daily incidence of stroke on single-lag days 19 - 24 and multi-lag days 0 - 24 to 0 - 26 among Shanghai residents, particularly affecting male individuals and those aged 60 years or older.